(untitled) (Revista Contexto & Educação, 2022)
The work presents results of the reconstruction of a training action planned as a way of contextualizing disciplinary knowledge of physics in the context of an Integrated Food Technician Course, which initially sought to evaluate the potential of integrating disciplinary knowledge through practical application. of an artisanal dryer. The interaction between teachers from different curricular units, one from the common core and the other from the professional, resulted in the negotiation for an integrative training action, which would be materialized in the form of a course conclusion work, exploring a proposal for the practical application of physical concepts in methods artisanal food drying. In the third semester of the course, the students began a process of knowledge interaction and in the sixth semester, they sought to integrate them in the execution of a practice using the artisanal food dryer. The results obtained indicate that the activities based on the use of the artisanal fruit dryer have the potential to promote an interdisciplinary construction of knowledge as recommended by the proposal of professional technical education, but it needs a planning of how to provoke an effective integration of previous knowledge about study. heat in food drying.